Diphtheria toxin and its ADP-ribosyltransferase-defective homologue CRM197 possess deoxyribonuclease activity. - Bruce, C (1990)
The cytotoxic mechanism of diphtheria toxin (DTx) is associated with its ability to inhibit protein synthesis by ADP-ribosylation of elongation factor 2. Although DTx intoxication leads to internucleosomal DNA cleavage and cell lysis, these events do not occur when protein synthesis is inhibited by alternative treatments (e.g., cycloheximide). Here we show that endonucleolytic degradation of DNA is an intrinsic activity of DTx and also of the crossreactive mutant protein CRM197. Assays using DNA-impregnated gels as well as linear and supercoiled DNA in solution revealed not only that CRM197 has nuclease activity but also that its specific activity is actually significantly greater than that of the wild-type molecule. Since CRM197 contains a single amino acid substitution that renders it incapable of ADP-ribosylation, we propose that the active sites for ADP-ribosyltransferase and nuclease activities are distinct.